PDCT-01. BIOLOGICAL MEDICINE FOR DIFFUSE INTRINSIC PONTINE GLIOMAS ERADICATION (BIOMEDE): RESULTS OF THE THREE-ARM BIOMARKER-DRIVEN RANDOMIZED TRIAL IN THE FIRST 230 PATIENTS FROM EUROPE AND AUSTRALIA. (11th November 2019) - Grill, Jacques; Le Teuff, Gwenael; Nysom, Karsten; Blomgren, Klas; Hargrave, Darren; McCowage, Geoff; Bautista, Francisco; van Vuurden, Dannis; Dangouloff-Ros, Volodia; Puget, Stephanie; Varlet, Pascale; Debily, Marie-Anne; et al.
Abstract: BACKGROUND: Diffuse intrinsic pontine glioma (DIPG) is one of the most devastating brain neoplasms. Despite 50 years of clinical trials, no improvement of survival has been observed and most children die within 2 years of diagnosis. Only radiotherapy transiently controls disease progression. METHODS/AIMS: BIOMEDE was conceived as a randomized multi-arm multi-stage program (drop-the-loser adaptive design). It started with an open-label phase-II trial comparing three drugs (everolimus, dasatinib, erlotinib) combined with irradiation, allocated according to the presence of their specific targets) with a planned sample size of 250 patients. A stereotactic biopsy was performed at diagnosis to centrally confirm the diagnosis of DIPG (presence of histone H3K27M mutation or loss of K27 trimethylation) and assess biomarkers/targets (PTEN-loss, EGFR-overexpression). Targeted therapies were started concomitantly with radiotherapy and were continued until disease progression. The main objective of the study was to compare the efficacy of randomized groups in terms of overall survival (OS). RESULTS: At the 3 rd interim analysis, based on 193 randomized patients among the 230 study patients, the IDMC concluded that the study was unlikely to meet its primary objective even if 250 patients were randomized. The median OS from the time of randomization was 10.9, 9.5 and 9 months for everolimus, dasatinib and erlotinib, respectively, which is comparable to historical controls. The median number of courses administered was 7, 5.5 and 6 respectively. Treatment was discontinued due to toxicity in 2%, 13%, and 15%, respectively. No biopsy-related death was reported and diagnostic yield was excellent, with only 5 non-informative biopsies. CONCLUSION: BIOMEDE shows the feasibility of biologically-driven treatment in DIPG on a large international scale. Based on the better toxicity profile and the slightly better efficacy, although not statistically significant, the steering committee proposed that everolimus should be used as the control arm for the next step, BIOMEDE 2.0.